The relationship between savings and economic growth in countries with different level of economic development - Piotr Misztal (e-Finanse: Financial Internet Quarterly, 2011)
The aim of this paper is to analyze the cause and effect relationship between economic growth and savings in advanced economies and in emerging and developing countries2. In this work we used the method based on studies in macroeconomics and international finance as well as econometric methods (co-integration models and Granger's causality test). All statistical data used in this paper came from the International Monetary Fund database (World Economic Outlook database). The results confirmed the existence of one-way casual relationship between gross domestic savings and gross domestic product in the case of developed countries as well as in developing and transition countries. At the same time it was revealed the absence of causal relationship between gross domestic product and gross domestic savings both in developed economies and developing and transition countries.
Keywords: D91; E21; 330; savings; economic growth; co-integration